Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

If an original conditional statement is represented using [tex]\( p \rightarrow q \)[/tex], which represents the converse?

A. [tex]\( \sim p \rightarrow \sim q \)[/tex]
B. [tex]\( -q \rightarrow -p \)[/tex]
C. [tex]\( q \rightarrow p \)[/tex]
D. [tex]\( p \rightarrow q \)[/tex]


Sagot :

To solve the problem of identifying the converse of a given conditional statement [tex]\( p \rightarrow q \)[/tex], let's follow these steps:

1. Understand the conditional statement [tex]\( p \rightarrow q \)[/tex]:
- Here, [tex]\( p \)[/tex] is the hypothesis or antecedent.
- [tex]\( q \)[/tex] is the conclusion or consequent.
- The statement reads as "If [tex]\( p \)[/tex], then [tex]\( q \)[/tex]."

2. Define the converse of [tex]\( p \rightarrow q \)[/tex]:
- The converse of a conditional statement [tex]\( p \rightarrow q \)[/tex] is obtained by reversing the hypothesis and conclusion.
- Thus, the converse is [tex]\( q \rightarrow p \)[/tex].
- The converse reads as "If [tex]\( q \)[/tex], then [tex]\( p \)[/tex]."

3. Examine the given options to identify which one represents the converse:

- Option 1: [tex]\( \sim p \rightarrow \sim q \)[/tex]
- This means "If not [tex]\( p \)[/tex], then not [tex]\( q \)[/tex]."
- This is actually the inverse of the original statement, not the converse.

- Option 2: [tex]\( - q \rightarrow - p \)[/tex]
- This notation seems to be another way to denote the inverse. However, it's unusual and not standard.

- Option 3: [tex]\( q \rightarrow p \)[/tex]
- This is the direct form of the converse. It means "If [tex]\( q \)[/tex], then [tex]\( p \)[/tex]", which matches our definition of the converse.

- Option 4: [tex]\( p \rightarrow q \)[/tex]
- This is the original conditional statement itself and not the converse.

4. Conclusion:
- Based on our reasoning, the correct option that represents the converse of [tex]\( p \rightarrow q \)[/tex] is [tex]\( q \rightarrow p \)[/tex].
- Thus, the answer is: [tex]\(\boxed{3}\)[/tex].
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.